Bibliometric analysis of scientific production in badminton - Blanca-Torres, J. C.; Ortega, E.; Nikolaidis, P. T.; Torres-Luque, G. (Journal of Human Sport & Exercise, 2020)
The aim of the present study was to analyse the scientific production in the sport of badminton. Publications were collected from the main collection of "Web of Science" platform, specifically from Science Citation Index Expanded (SCI-EXPANDED), Social Sciences Citation Index (SSCI) and Art & Humanities Citation Index (A&HCI) databases for the period 2007-2017, obtaining a total of 122 items. The analysis assessed annual trend of published articles from 2007 to 2017, country distribution of publications, first author`s institution distribution of publications, first author`s productivity, average number of authors per article, major journals, average number of citations per article, thematic area, sample characteristics and modality. Among the most relevant conclusions are the number of publications on badminton has increased significantly from 2007 to 2017, more specifically in the last 4 years (2014-2017); Asian and European countries have the highest productivity index, both continents with great trend in badminton, coinciding, in turn, with institutions and first authors; health and training are the most studied thematic areas, whose main disciplines are sports medicine and theory of sports training. This type of studies provides baseline information on future research directions in badminton.